Analysis of Corruption Criminal Punishment Based on Qawāid Fiqhiyyah - Rahmawati, Lutfia; Multazam , Umar (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
This study uses an Islamic approach with a fiqh perspective based on Qawāid Fiqhiyyah to address corruption. This means they combine subjective (based on Islamic views), primordialist (rooted in Islamic religious and cultural identity) and dogmatic (based on strictly applied Qawāid Fiqhiyyah principles) approaches to deal with the complex and dilemmatic problem of corruption. This approach allows them to treat corruption not just as a legal crime, as well as a moral and social problem that needs to be resolved by taking into account religious values ​​​​and the principles of justice and public benefit regulated in Qawāid Fiqhiyyah. In the context of Qawāid Fiqhiyyah, this approach reflects the main principles that focus on justice, community welfare and prevention of damage. Qawāid Fiqhiyyah emphasizes the importance of fair and efficient law enforcement (الضرر يزال - "damage must be eliminated"), maintaining the public benefit (المصلحة العامة - "public interest"), and maintaining moral and religious values ​​(الأمور بمقاصدها - "everything is based on goals"). Confirming the law, improving the economic conditions of officials, and overcoming the culture of hedonism and consumerism are in line with these principles, which ultimately aim to create a just and prosperous society.